2008
DOI: 10.1080/13554790701851551
|View full text |Cite
|
Sign up to set email alerts
|

Brain Integrity and Cerebral Atrophy in Vietnam Combat Veterans with and without Posttraumatic Stress Disorder

Abstract: Posttraumatic stress disorder (PTSD) is associated with decreased hippocampal volume, but the relationship between trauma and brain morphology in the absence of PTSD is less clear. In this study, measures of brain integrity were determined by estimating gray and white matter regional brain volumes using structural magnetic resonance imaging in six patients with PTSD and in five controls with comparable trauma exposure but without clinical evidence of PTSD. The only statistically significant volume difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…Second, stress/distress increases the activity of the hypothalamic-pituitary-adrenal axis and thus the levels of glucocorticoid hormones (22), which may cause structural and functional damage to the brain, especially in the medial temporal lobe (23,24). Third, animal studies suggest that increased glucocorticoid levels and chronic stress may increase the deposition of A-amyloid peptide and T-protein in the brain (25Y27), which may result in neurodegeneration (28). Fourth, psychological stress and distress may also cause structural and functional brain changes via increased activity of catecholamines and cytokines in the brain (2,29).…”
Section: Discussionmentioning
confidence: 97%
“…Second, stress/distress increases the activity of the hypothalamic-pituitary-adrenal axis and thus the levels of glucocorticoid hormones (22), which may cause structural and functional damage to the brain, especially in the medial temporal lobe (23,24). Third, animal studies suggest that increased glucocorticoid levels and chronic stress may increase the deposition of A-amyloid peptide and T-protein in the brain (25Y27), which may result in neurodegeneration (28). Fourth, psychological stress and distress may also cause structural and functional brain changes via increased activity of catecholamines and cytokines in the brain (2,29).…”
Section: Discussionmentioning
confidence: 97%
“…[42][43][44] Of the 12 cross-sectional studies examining the hippocampus in veterans with chronic CR-PTSD, 9 found a significantly smaller volume in either or both hippocampi, 18,[21][22][23]25,30,33,34,36 and 3 found no significant volume differences. 24,29,32 Studies that found a smaller total or right hippocampus were more numerous and of higher quality than those that did not (see Table 1). The positive studies were generally of greater size than the negative studies (average for positive findings: N=53.7; average for negative findings: N=15.7), and eight of the nine controlled for alcohol abuse.…”
Section: Review Processmentioning
confidence: 93%
“…The positive studies were generally of greater size than the negative studies (average for positive findings: N=53.7; average for negative findings: N=15.7), and eight of the nine controlled for alcohol abuse. Two of the three Gilbertson et al; 9 Gurvits et al; 22 Hedges et al; 23 Kasai et al; 25 Pavi c et al; 30 Vythilingam et al; 33 Wang et al; 34 Woodward et al 36 30 3.33 (3) Hedges et al; 24 Neylan et al; 29 Schuff et al 32 6 2.00…”
Section: Review Processmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, because these men had been in war it was important to have as a control, not a 'clean' control sample with no history of military service or injury, rather one who had experienced the trauma of war and sustained peripheral injury, but not a brain injury. Of course, this long predates any association of brain pathology that can accompany post traumatic stress disorder (PTSD; see Hedges et al 2007), but nonetheless recognized as having a control sample as closely matched as the experimental group in terms of experience and background, except for the variable of a brain lesion.…”
Section: Lessons From Teuber's Classificationmentioning
confidence: 99%